CHILD MORTALITY IN ANCIENT ROME AND MODERN IBADAN (2013)
High records of occurrences of child mortality were documented in ancient Rome and in modern Ibadan. Available studies on ancient Rome focused on the effect of female infanticide on the population, and those on modern Ibadan, concentrated on the effects of cerebral malaria on children below the age of 5. However, these studies ignored the comparative possibility of health situations in both societies despite their related experiences. This study, therefore, compared the causes of child mortality (ages 0-5) in both societies. The study employed historical and comparative methodologies to highlight the factors that caused child mortality in both societies. Sources utilised on ancient Rome were volume X of the Corpus Inscriptionum Latinarum, from which gender distribution of mortality and chronological age of children were gleaned. Data were also extracted from classical and contemporary authors. For modern Ibadan, information was gathered from medical literature and newspaper reports. The data were subjected to content analysis. The factors which brought about child death in ancient Rome and modern Ibadan were similar, but they occurred in varying degrees of magnitude. Respiratory tract infections such as pneumonia, acute bronchitis, asthma, and tonsillitis caused child mortality in both societies. Air-borne and water-borne diseases such as tuberculosis, cholera, typhoid, measles and diarrhea killed children below age 6. These diseases were often aggravated by malaria. Dysentery and inflammatory bowel diseases such as entiritis also accounted for children’s death. Other diseases that included jaundice, malaria, convulsions, neo-natal tetanus, meningitis, severe malnutrition, severe birth syphxia, ulcers and gangrene also caused child mortality in both societies. Maternal illiteracy, superstitious beliefs, social deprivation, and poverty were the social and economic factors which permitted child mortality in the two civilisations. In both societies, children less than 3 were worst affected by these diseases due to their vulnerability. In ancient Rome, neo-natal death resulting from venereal diseases such as gonorrhea and syphilis were transferred from mother to child at birth, but this death was rare in modern Ibadan since people were informed of the disease in modern Ibadan than in antiquity. Lead poisoning, superstitious beliefs and social deprivation caused death in both societies. In ancient Rome, social deprivation ranked highest, followed by superstitious beliefs and lead poisoning because of government’s enthusiasm about the empire’s consolidation. In modern Ibadan, superstitious beliefs caused more death than lead poisoning and social deprivation due to the people’s belief system. While malaria and tuberculosis killed thousands of children than other diseases in ancient Rome, neonatal tetanus, prematurity and low birth weight, neonatal septicaemia and severe birth sphyxia ranked highest in modern Ibadan. They ranked highest in antiquity and Ibadan respectively due to weather conditions and people’s ignorance of the diseases. Child mortality in ancient Rome and modern Ibadan was caused by tropical diseases, sexually transmitted infections and respiratory tract infections. Thus, child mortality was a social challenge in both societies. Further studies could examine the divergence and convergence in the medical approaches applied to infant diseases in ancient Rome and modern Ibadan.